2013
DOI: 10.1002/stem.1462
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic stem cells neural differentiation qualifies the role of Wnt/β-Catenin signals in human telencephalic specification and regionalization

Abstract: Wnt-ligands are among key morphogens that mediate patterning of the anterior territories of the developing brain in mammals. We qualified the role of Wnt-signals in regional specification and subregional organization of the human telencephalon using human pluripotent stem cells (hPSCs). One step neural conversion of hPSCs using SMAD inhibitors leads to progenitors with a default rostral identity. It provides an ideal biological substrate for investigating the role of Wnt signaling in both anteroposterior and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
100
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(120 citation statements)
references
References 53 publications
(60 reference statements)
4
100
0
Order By: Relevance
“…The activin-induced gene expression changes are distinct from those induced by Shh, which is the key molecule employed by published striatal differentiation protocols (Aubry et al, 2008;Ma et al, 2012;Nicoleau et al, 2013). These studies and the current work show that Shh elicited a strong inductive effect on MGE regulator genes, such as NKX2.1, and gene markers expressed in both the MGE and LGE (e.g.…”
Section: Activin Promotes An Lge Phenotypesupporting
confidence: 58%
See 1 more Smart Citation
“…The activin-induced gene expression changes are distinct from those induced by Shh, which is the key molecule employed by published striatal differentiation protocols (Aubry et al, 2008;Ma et al, 2012;Nicoleau et al, 2013). These studies and the current work show that Shh elicited a strong inductive effect on MGE regulator genes, such as NKX2.1, and gene markers expressed in both the MGE and LGE (e.g.…”
Section: Activin Promotes An Lge Phenotypesupporting
confidence: 58%
“…Shh was first applied in an hESC differentiation protocol for generating DARPP32 + neurons (Aubry et al, 2008) and again recently with or without combinatorial inhibition of Wnt signalling (Ma et al, 2012;Carri et al, 2013;Nicoleau et al, 2013). The effect of Shh on the generation of ventral forebrain cellular phenotypes might be due to the derepression of GLI3, which is a key factor that dorsalises hESC-derived neural progenitors (Li et al, 2009).…”
Section: Differential Activity Of Activin and Shh In Regulating Ventrmentioning
confidence: 99%
“…However, many other reports highlight the role of canonical Wnt signaling in stem/progenitor cell maintenance, rather than induction of differentiation. For example, Wexler et al showed that baseline -catenin signaling represses neuronal differentiation in human NSCs [131], and another study reported that inhibition of Wnt/ -catenin signaling using Dkk-1 or the tankyrase inhibitor XAV939 promotes neural precursor specification [164]. Moreover, GSK-3 inhibition, which induces stem cell renewal and sustains the expression of pluripotency markers [16], is a widely used tool to expand neural progenitors 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 [154][155][156], and bFGF treatment of hES and iPS cells, which maintains the undifferentiated state, activates canonical Wnt signaling through inhibition of GSK-3 [165].…”
Section: Human Neural Stem and Progenitor Cells: Intracellular Componmentioning
confidence: 99%
“…Specifically, addition of both noggin and SB431542 (a BMP inhibitor and Activin/Nodal inhibitor, respectively) was shown to increase the yield of cells expressing the neural markers Pax6, Foxg1 and Sox1, whilst expression of the pluripotent marker Oct4 decreased [72]. This method is now widely used as the first stage in the generation of neural cells from PSCs and has successfully been applied to the initial stages of striatal differentiation protocols [73][74][75] (discussed below, and see Table 1). …”
Section: Directed Differentiation Of Pscs Towards Striatal Msnsmentioning
confidence: 99%